Enhanced photothermal reduction of gaseous CO2 over silicon photonic crystal supported ruthenium at ambient temperature. Issue 12 (16th October 2018) - O'Brien, Paul G.; Ghuman, Kulbir K.; Jelle, Abdinoor A.; Sandhel, Amit; Wood, Thomas E.; Loh, Joel Y. Y.; Jia, Jia; Perovic, Doug; Singh, Chandra Veer; Kherani, Nazir P.; Mims, Charles A.; Ozin, Geoffrey A.
Abstract : Gaseous CO2 is transformed to CH4 at ambient temperature at high rates under intense solar-simulated radiation over sputtered Ru supported on Si-based photonic crystals. Abstract : Solar-driven CO2 hydrogenation can provide a renewable source of fuels and reduce greenhouse gas emissions if operated at industrial scales. Herein we investigate the photomethanation (light-driven Sabatier reaction) rates over Ru films sputtered onto silica opal (Ru/SiO2 ) and inverted silicon opal photonic crystal (Ru/i-Si-o) supports at ambient temperature under solar-simulated radiation as a function of incident light intensity. Photomethanation rates over both the Ru/SiO2 and Ru/i-Si-o catalysts increase significantly with increasing light intensity, and rates as large as 2.8 mmol g −1 h −1 are achieved over the Ru/i-Si-o catalyst. Furthermore, the quantum efficiency of the photomethanation reaction is almost three times larger when measured over the Ru/i-Si-o catalyst as compared to the Ru/SiO2 catalyst. The large photomethanation rates over the Ru/i-Si-o catalyst are attributed to its exceptional light-harvesting properties. Moreover, we perform DFT analysis to investigate the potential role of photo-induced charges on the Ru surface. The results from the simulation indicate that charged Ru surfaces can destabilize adsorbed CO2 molecules and adsorb and dissociate H2 such that it can readily react with CO2, thereby accelerating the Sabatier reaction.